Influence of natural vegetation on soil arthropods on olive tree in the north of Portugal. - Pereira, J.A. (2004)
Several works reported that the habitat can be an important factor in retaining predators in a system and can affect predators’ efficiency and enhancing biological control. The aim of this work was to study the effect of soil cover with natural vegetation in comparison to the traditional tillage on soil arthropods of the olive grove.